ANALISIS PERAN KEPEMIMPINAN CAMAT DALAM MENINGKATKAN KINERJA PEGAWAI PADA KANTOR KECAMATAN KENDARI BARAT - Desriani Safitri; Samdin; Hastuti; La Hatani; La Ode Bahana Adam; Aidin Hudani Awasinombu (Jurusan Manajemen FEB UHO, 2024)
This research aims to find out and analyze the role of the sub-district head's leadership in improving employee performance at the West Kendari sub-district office. The study involved five informants working at the West Kendari Sub-district Office. The research indicators used include: The Interpersonal Role: Figurehead, Leader, Liasion. The Informational Role: Monitor and Dessiminator, Spokes Person. The Decision Making Role: Entrepreneur, Distrubance Handler, Resource Allocation, Negotiator. Additionally, nine questions related to the sub-district head’s leadership role in enchancing employee performance were examined. The analysis employed is Deskriptif Qualitative, utilizing data sourced from informants and documentation from the WestKendari Sub-district Office. The results of this study indicate that the role of the sub-district head’s leadership in improving employee performance, according to Henry Mintzberg’s theory is quite effective. The interpersonal role involves providing direction, motivation, and training to employees. The informational role is executed with openness in listening to employees opinions. Lastly, The decision making role involves engaging employees before making policy decisions.